Food security in the context of environmental risks: Public perception assessment - Detelić, Romana; Jovičić, Nives; Matin, Ana; Črnko, Marina; Skendrović, Kruno (Crisis Management Days, 2024)
Factors such as climate change, changes in plant and animal life, and the spread of diseases have an increasing impact on food production, which can lead to serious consequences for food security. The paper explores the complex issues of food security in relation to environmental impacts and associated risks. Through an analysis of various environmental challenges, such as climate change and environmental pollution, the paper explores the associated risks and potential consequences for food systems. Additionally, it investigates the increased risks of disease spread, contamination of food by chemicals and microorganisms, and the depletion of essential resources for food production. Furthermore, this paper presents the outcomes of a survey aimed at understanding and analyzing public perceptions of food security within the context of environmental risks. Through the analysis of citizens’ perceptions, it investigates how people perceive these risks and what their attitudes and concerns are. According to the research results, the majority of respondents are aware of environmental pollution and its impact on food security. Almost all respondents believe that environmental risks affect food security, and that pollution affects food quality, with almost 50% of respondents changing their food and beverage consumption habits due to concerns about environmental risks and noticing changes in the quality and availability of certain foods.